Critical biomass harvesting indicator for whole-tree extraction does not reflect the sensitivity of Swedish forest soils. (December 2021) - Löfgren, Stefan; Stendahl, Johan; Karltun, Erik
Highlights: The critical forest biomass harvest (CBH) and critical load concepts are similar. The CBH indicator does not account for all relevant processes. CBH correlates poorly to forest soil acid-base status and edaphic conditions. CBH cannot be used for management advice to forest owners. CBH does not fulfill the demands for forest biomass harvesting guidelines. Abstract: There is a growing societal demand to increase the use of forest biomass for substitution of fossil fuels. The production of this biomass must be sustainable and an indicator for critical biomass harvesting (CBH) has been suggested in order to sustain forest soil fertility and mitigate soil acidification at whole-tree harvesting. The CBH indicator is based on an acidity mass balance approach in line with the critical load of acid deposition (CL) concept. Countries like Sweden, the Netherlands and the state of Quebec, Canada apply such mass balance approaches for developing forest biomass harvesting guidelines. The implementation of this type of policy instrument may restrict the use of harvest residues for bioenergy and thereby the substitution of fossil fuels. It may as well affect the forestry sector revenue negatively. To maintain credibility for enforced limitations, it is important that the risk assessment and suggested policy implications are based on solid scientific methods and assumptions. The mass balance approach have been criticized for being too uncertain and not sufficiently validated for being used to guide ecosystem management. In this paper we use published Swedish data on soils, acid deposition, forest production and information from international scientific literature to critically examine the CBH indicator. We conclude that the CBH indicator 1) does not account for all relevant processes 2) it exaggerates the sensitivity and correlates poorly to actual forest soil acid-base status and edaphic conditions and 3) data availability does not allow the indicator to be calculated at a high enough spatial resolution for advice on management for forest owners. The concerns for the mass-balance approach and CBH indicator are discussed in an international perspective.